PROBLEMATIKA PEMBELAJARAN AQIDAH AKHLAK: ANTARA KONSEP NORMATIF DAN REALITAS PRAKTIK - Ermiza Ermiza; Nurhayani Nurhayani; Fitri Alrasi (CV. ADIBA AISHA AMIRA (ADISAM PUBLISHER), 2026)
Aqidah Akhlak learning has a strategic role in shaping the faith and character of students in accordance with the values of Islamic teachings. However, in practice, learning Aqidah Akhlak often faces various problems that cause a gap between the ideal normative concept and the reality of practice in educational institutions. This study aims to examine and analyze the problems of learning Aqidah Akhlak by examining the relationship between the normative foundation of Islamic teachings and the implementation of learning in the field. This research uses a qualitative approach with the library research method, with data sources in the form of books, scientific journals, academic articles, as well as relevant Islamic education policy and curriculum documents. Data is analyzed using content analysis techniques through the process of data reduction, theme categorization, and conclusion drawn. The results of the study show that the learning problems of Aqidah Akhlak are influenced by various factors, such as learning approaches that are still cognitive, limited integration of values in daily practice, and lack of contextualization of the material with the social reality of students. This research is expected to make a theoretical contribution as a reflection material and the basis for the development of learning Aqidah Akhlak that is more contextual, integrative, and applicative.